PRODUK KEWIRAUSAHAAN DARI LIMBAH BIJI RAMBUTAN DESA SUKOSARI DUSUN PULOSARI KASEMBON - Shinta Nuriyatul Lailiyah; Rayno Dwi Adityo; Salmannisa Najah Ali; Zahara Salsabila; Mohammad Tegar Firdaus; Rahmatullah Alaik Marzuki (DEVOSI, 2023)
The need for food in human life affects food sources that continue to increase. As one of the efforts that can be made by utilizing local potential that can be processed into food products for the abundance of existing potential. Judging from the local potential of Dusun Pulosari Kasembon East Java in the form of rambutan plants planted in the yard of the house as a shade tree. During the rambutan season, residents only use the fruit for personal consumption and sale. Meanwhile, rambutan seeds (Nephelium sp) can be used as side products, such as the popular rambutan seed chips and nuts. The method used in this activity was in the form of training (socialization) which was carried out as part of Group 115 KKM activities which were primarily aimed at the people of Pulosari Hamlet, Kasembon District. The purpose of this activity is as a form of education and training for residents in processing rambutan seeds into chips and rambutan seed nuts which will later be developed and sold to the general public. The result of this training is to provide knowledge and convenience for residents to utilize rambutan seeds which have not been used so far so that they become a commodity of economic value.